Revisiting tax management determinants: the interplay of capital intensity, liquidity, and firm size in Indonesia - Erawati, Teguh; Safitri, Nela; Listyawati, Reni (Proceeding International Conference on Accounting and Finance, 2026)
This study aims to examine the effect of financial aspects, namely capital intensity and liquidity, on tax management practices in manufacturing companies in Indonesia. In addition, this study also examines the role of company size as a moderating variable that can strengthen or weaken the relationship between independent variables and tax management. A quantitative method with a purposive sampling approach was used to sample 204 years of companies from their financial reports during the 2019-2024 period. The data were analyzed using statistical techniques with the EViews application. The results showed that capital intensity and liquidity did not have a significant effect on tax management. Furthermore, company size proved to be a moderating variable that influenced the strength of this relationship. These findings provide theoretical and practical contributions to corporate tax strategy management, particularly in the context of companies in Indonesia, and provide insights for managers and decision makers on efficient financial and tax management.